Studi tentang perilaku pencarian informasi pada official account line KABIM Universitas Padjadjaran: Surver Deskriptif tentang perilaku pencarian informasi mahasiswa - Debora Sitorus; Yunus Winoto; Saleha Rodiah (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2020)
This research explained about college student’s information seeking behavior through LINE Kabim Universitas Padjadjaran Official Account. The purpose of this research is to obtained information about college student’s information seeking behavior through LINE Kabim Universitas Padjadjaran Official Account according to information search process model by Carol Khulthau. Khulthau divided information search process into 6 stages: initiation, selection, exploration, formulation, collection, and presentation. This research is quantitative method with descriptive analysis survey. The data were collected by using questionnaire, interview, and literature study. The population of this research was Universitas Padjadjaran college students who add LINE Kabim Universitas Padjadjaran Official Account. This research used quota based sampling and obtained 99 Bidikmisi scholarship recipients as respondent in total. Based on research finding the result of respondents’ initiation process is high, respondents’ selection process is high, respondents’ exploration process is high, respondents’ formulation process is high, respondents’ collection process is high, and respondents’ presentation process is high.